Social Activism and Societal Transformation: Assessing the Impact of Human Rights Movements - Ade Risna Sari; Gamar Al Haddar (West Science Social and Humanities Studies, 2023)
This research employs bibliometric analysis to examine the impact of the Human Rights Movement on social activism and societal transformation. Through the utilization of the VOSviewer software, a systematic assessment of scholarly publications was conducted to uncover trends, collaborations, and influential works in this dynamic field. The analysis revealed distinct thematic clusters, including those centered around conflict, culture, business, health, and basic human rights. Seminal works, such as "Activists Beyond Borders" and "Racial Formation in the United States," were identified as pivotal in shaping the discourse. The distribution of term occurrences highlighted a focus on practice, human rights activists, traditional justice, and education. This study contributes to a comprehensive understanding of the multidimensional relationships between human rights, activism, and societal transformation, providing insights for academics, policymakers, and activists alike.